Application of Self-Reflection Using Reflective Journal on Oxytocin Massage Skills in Diploma Three Midwifery Students - Arbie, Rina Sulisthia; Budu, Budu; Ahmad, Mardiana; Bukhari, Agussalim; Alasiry, Ema; Usman, Andi Nilawati (JURNAL INFO KESEHATAN, 2023)
Midwifery is a profession based on women-centered and evidence-based care through the provision of mutually respectful professional relationships and partnerships. To train students' skills, repeated learning is needed, learning can be sourced from experiences such as doing self-reflection by keeping a reflective journal. This research aims to analyze the effect of applying self-reflection using a reflective journal on oxytocin massage skills. This research is an experimental research using a one-group pretest-posttest group design approach, taking samples using a simple random sampling technique. The research population was all level III students in a bivariate analysis using the Friedman ANOVA test. The results showed that the pretest mean value was 59.28 increasing to 79.50 in the first posttest and 83.38 in the second posttest with a p-value <0.05, which means that there is an effect of applying reflective journals using reflective journals on oxytocin massage skills. Having students write reflective journals is a great way for them to learn new concepts. This approach is also useful for lecturers to get feedback on the concepts being studied by students. The use of reflective journals will guide students to analyze what they have and do not know about the material being studied and how to overcome the obstacles encountered so that learning goals are achieved and foster independent learning in students.